Pembuatan dan pengujian spot welding menggunakan travo daur ulang - Tri Cahyo Wahyudi; Asroni Asroni; Bahtiar Abdul Rahman (TURBO [Tulisan Riset Berbasis Online], 2022)
Spot welding is very much needed for the home industry, but the expensive welding price and large welding power make spot welding less efficient for small industries. Therefore, spot welding with small power and easy-to-carry design is needed. Spot welding design process is carried out in stages, namely planning, explaining component functions, and testing variations in the welding time used. The method used is experimental by making and testing. The specimen used is a type 304 stainless steel plate with a thickness of 0.8 mm. selected stainless steel type 304 with a thickness of 0.8 mm using a lap joint, with variations in welding time of 10, 15, and 20 seconds, using a current of 550 Ampere. The test carried out is a shear test with the AWS D8.9-97 test standard, with the aim of this study to determine the optimization of spot welding equipment using a recycled transformer on the test results. From the results of the research that has been carried out, it can be concluded that in variations of electric current and welding time, the highest average shear stress value is found at 550 A electric current by welding for 10 seconds the average shear stress is 1,060,164 (N/mm²) and the lowest average shear stress at an electric current of 550 A welding for 20 seconds the average shear stress is 564.578 (N/mm²).